Geochemistry of the pre/syn-metamorphic granite in the Ongul Islands, East Antarctica - Kawano, Yoshinobu; Meno, Akihiro; Nishi, Naoko; Kagami, Hiroo (National Institute of Polar Research, 2005)
P(論文) Latest Proterozoic to Early Paleozoic pre/syn- and post-metamorphic granites occur in the Lutzow-Holm Complex (LHC), East Antarctica. The pre/syn-metamorphic granites in the Ongul Islands consist of biotite hornblende (BH) granite and garnet biotite hornblende (GBH) granite. The Rb-Sr whole rock isochron age of 580±23Ma with an initial ^(87)Sr/^(86)Sr ratio of 0.70784±0.00059 is obtained from the BH granite. This age is slightly older than SHRIMP U-Pb zircon and CHIME monazite metamorphic ages (520-550Ma) from the complex. The BH granite has lower aluminum saturation index than the GBH granite. The pre/syn-metamorphic granites have a wide variation of εSr and εNd values at 580m.y. before the present, and the BH granite has lower εSr_(580Ma) and higher εNd_(580Ma) values than the GBH granite. One end of the variations in the ε diagram is close to the values of the mafic to intermediate metamorphic rocks in the island; the other is close to those of the old continental crust. These geochemical and isotopic features suggest that the PSMGs were originated by mixing between magma derived from mafic to intermediate metamorphic rocks and old continental crust. departmental bulletin paper